Covid-19 Vaccination: Rights or Obligations? - Saija, Vica Jillyan Edsti (Faculty of Law, Universitas Pattimura, 2021)
In responding to the pandemic due to the coronavirus, the Indonesian government requires the public to carry out vaccinations in order to prevent the spread of the coronavirus and establish herd immunity. This instruction contradicts that health is a form of human right that cannot be enforced. Therefore, this paper wants to examine whether COVID-19 vaccination in the midst of an pandemic situation is a form of human right or obligation. The research method used in this paper is a normative method, and the results of this paper indicate that the covid-19 vaccine during an pandemic period can be categorized as a form of human obligation for everyone based on the obligation to respect the human rights of others as stated in the State Constitution. The Republic of Indonesia in 1945.